Effectiveness of Proton-Pump Inhibitors in Chronic Obstructive Pulmonary Disease: A Meta-Analysis of Randomized Controlled Trials - Yu, Fei; Huang, Qihui; Ye, Yousheng; Zhang, Lin (Frontiers in Medicine, 2022)
Abstract Background: Although several randomized controlled trials (RCTs) have been published in recent years, the role of proton-pump inhibitors (PPI) in patients with chronic obstructive pulmonary disease (COPD) remains controversial. This preliminary meta-analysis was conducted to evaluate the clinical efficacy of PPI in patients with COPD. Methods: RCTs related to PPI in the treatment of patients with a definite diagnosis of COPD were enrolled in this meta-analysis. PubMed, Embase, Cochrane Library, CNKI, Wanfang and VIP databases were retrieved to identify eligible studies from database establishment to September 22, 2021. Two researchers independently screened the articles, extracted the data and evaluated the risk of bias in the included studies independently. The study complied with PRISMA 2020 guideline for this study. The meta-analysis was performed using RevMan5.3. Heterogeneity among studies was tested using the I2 test. The results were presented as risk ratios (RRs) with 95% confidence intervals (CIs). Results: A total of 15 RCTs, including 1684 patients, were enrolled. The meta-analysis revealed that PPI plus conventional treatment was superior to conventional treatment with respect to the case fatality rate (RR=0.30; 95% CI, 0.18–0.52; P<0.001), the incidence of gastrointestinal bleeding (RR=0.23; 95%CI, 0.14–0.38; P<0.001), the incidence of other adverse reactions (RR=0.33; 95%CI, 0.28–0.39; P<0.001) and the number of acute exacerbations (mean difference [MD]=-1.17; 95% CI, 1.75–-0.60: P<0.001) in patients with COPD. No significant differences were found in clinical efficacy (RR=1.08; 95%CI, 0.95–1.22; P=0.25), FEV1/FVC (MD=3.94; 95%CI, -8.70–16.58; P=0.54) and nosocomial infection rate (RR=1.31; 95%CI, 0.57–3.00; P= 0.52) between the two groups. Discussion: This comprehensive meta-analysis suggested that PPI treatment for COPD may reduce the case fatality rate, incidence of gastrointestinal bleeding and other adverse reactions and number of acute exacerbations. However, the present meta-analysis also has some limitations of the evidence, such as the high risk of bias of the included studies, and predominance of included studies from China, which may result in publication bias. Therefore, further large-scale RCTs are needed to confirm our findings.